Analysis of Operation Time of Sprinkler by RTI Value - Kim, Seo-Young; Kong, Ha-Sung (International Journal of Membrane Science and Technology, 2023)
In this study, a scenario was developed and studied to find out the change in the operation time of the sprinkler head according to the difference in the RTI value of the sprinkler head in the event of a fire in a partitioned space. The simulation results of the operation time according to the change in the RTI value of the sprinkler head are as follows. As a result of analyzing the operation time of the sprinkler head for each scenario, it was confirmed that the lower the RTI value, the faster the operation time, and in the case of Scenarios 2 and 3, the change of the RTI value is not significant, either. Also, the sprinkler head in the same position did not operate at the same time because the sprinkler head near the window position was slower. Therefore, it was confirmed that the sprinkler head with a low RTI value should be used in places with high risk when a fire occurs, and that the sprinkler head should be installed in a position where the wind effect is insignificant.